Life in lockdown: a longitudinal study investigating the impact of the UK COVID-19 lockdown measures on lifestyle behaviours and mental health - Solomon-Moore, Emma; Lambert, Jeffrey; Grey, Elisabeth; Gillison, Fiona; Townsend, Nick; Busam, Betty; Velemis, Kyriakos; Millen, Christopher; Baber, Fran; Griffin, Tania (BMC public health, 2022)
The COVID-19 pandemic led to the UK government enforcing lockdown restrictions to control virus transmission. Such restrictions present opportunities and barriers for physical activity and healthy eating. Emerging research suggests that in the early stages of the pandemic, physical activity levels decreased, consumption of unhealthy foods increased, while levels of mental distress increased. Our aims were to understand patterns of diet, physical activity, and mental health during the first lockdown, how these had changed twelve-months later, and the factors associated with change.
Gesehen am 15.11.2022